2022
DOI: 10.3390/app12062784
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Applications for Mobile Devices on the Practice of Physical Exercise in Adolescents

Abstract: The use of mobile devices has changed the way we relate to each other, influencing teaching–learning processes and the motivation of adolescents towards these processes. One of the most developed tools has been applications (apps), which are software used on cell phones, tablets or computers. Hence, the aim of this study is to analyze the content of applications for mobile devices that is considered the most suitable complement to Physical Education (PE) classes for secondary school students. A retrospective d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…Physical gamified practice favors sociability or socialization processes. In fact, studies such as those by the authors of [57][58][59]62,64,66,68] agree with the study described by the author of [73], who found better social functioning and good mental health in young adults. The author of [66] expressed concern about the toxic behaviors that can gestate in social networks.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Physical gamified practice favors sociability or socialization processes. In fact, studies such as those by the authors of [57][58][59]62,64,66,68] agree with the study described by the author of [73], who found better social functioning and good mental health in young adults. The author of [66] expressed concern about the toxic behaviors that can gestate in social networks.…”
Section: Discussionsupporting
confidence: 78%
“…The authors of [57,61,62,68,72] found that physical activity produces mental well-being. The same opinion was detailed in [26] regarding exergames, and this was due to the fact that this type of game decreases levels of stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the results obtained in the present study show that the use of mobile applications in the adolescent population aged 12–16 years old does not seem to have a significant effect on body composition and physical fitness of adolescents, which could be due to the lack of a significant increase in physical activity or daily steps through the use of mobile apps. Therefore, future research is needed that includes new mobile application designs that can be truly useful, as previous research has shown that the mobile apps currently on the market are not suitable for use in physical education classes, as they do not facilitate their didactic use (Alonso‐Fernández et al, 2022). This, together with the results obtained, should be considered in future research studies that use mobile apps, as the promotion of their use from physical education classes could have great potential, but not with the designs currently available on the market.…”
Section: Discussionmentioning
confidence: 99%
“…Some scholars have found that retirement makes lifestyle changes such as socializing, sleeping, smoking, and drinking, which affect one's health level. Our scholar Jinzhen Ye, on the other hand, argued that retirement will change habits that were developed in the short term, and for habits that have persisted over time cannot be changed by the event of retirement alone [5].…”
Section: Introductionmentioning
confidence: 99%